miRNA profiling in intrauterine exosomes of pregnant cattle on day 7 - Zhai, Yaying; Shi, Qiaoting; Chu, Qiuxia; Chen, Fuying; Feng, Yajie; Zhang, Zijing; Qi, Xinglei; Arends, Danny; Brockmann, Gudrun A.; Wang, Eryao; Lyu, Shijie (Frontiers in Veterinary Science, 2022)
Intrauterine exosomes have been identified to be involved in the embryo development and implantation. The aim of this study was to explore the role of miRNAs in intrauterine exosomes in bovine pregnancy. Intrauterine exosomes were collected from uterine flushing fluids of three donor and three recipient Xianan cows 7 days after fertilization. Expression levels of the exosomal miRNAs were analyzed. Sixty miRNAs differed significantly in their amounts between donors and recipients (p-value<0.05, |log2(FoldChange)|>1). Twenty-two miRNAs were upregulated and 38 downregulated in the group of donor cows. The bta-miR-184 was the most significant (PBenjamini-Hochberg <0.001). A total of 9,775 target genes were predicted using the 60 miRNAs. GO and KEGG analysis showed that the target genes were enriched in several biological processes or pathways associated with embryo implantation and endometrial development, such as cell adhesion, cell junction, focal adhesion, and Rap1 signaling pathway. Our findings suggest that, in cattle early pregnancy stage, these differently expressed miRNAs in intrauterine exosomes involved in embryo implantation and endometrial development, which may exert a significant effect and influence the uterine microenvironment for embryo implantation. These results could provide reference for screening and exploring the intrauterine exosomal miRNA affecting embryo implantation.